Thrusting and exhumation of the southern Mongolian Plateau: Joint thermochronological constraints from the Langshan Mountains, western Inner Mongolia, China. (15th August 2017) - Feng, Li-Xia; Brown, Roderick W.; Han, Bao-Fu; Wang, Zeng-Zhen; Łuszczak, Katarzyna; Liu, Bo; Zhang, Zhi-Cheng; Ji, Jian-Qing
Graphical abstract: Highlights: First constraint on the exhumation of the Langshan Mountains. Biotite/muscovite and K-feldspar 40 Ar/ 39 Ar, AFT, and AHe analyses. Individual and joint thermal history modelling. Impacts of thrusting on denudation. Abstract: The Mongolian Plateau has undergone multi-stage denudation since the Late Triassic, and the NE-trending Langshan Mountains in the southern margin of the Mongolian Plateau is crucial to unraveling the Meso-Cenozoic cooling and exhumation history of the Mongolian Plateau. The Langshan Mountains are dominated by Precambrian gneiss and Permian–Middle Triassic granitic plutons crosscut by a set of NE-striking thrust faults. A joint thermochronological study was conducted on 31 granitic and gneissic samples along the HQ and CU transects across the Langshan Mountains and other two samples from the BQ in the north of the Langshan Mountains. Four biotite/muscovite and three K-feldspar 40 Ar/ 39 Ar plateau ages range from 205 ± 1 to 161 ± 1 and 167 ± 1 to 131 ± 1 Ma, respectively. Thirty-three apatite fission track (AFT) ages are between 184 ± 11 and 79 ± 4 Ma, with mean track lengths from 11.1 ± 1.8 to 13.1 ± 1.4 μm of mostly unimodal distributions. Thirty-one single-grain raw AHe ages are in a range of 134 ± 8 to 21 ± 1 Ma. The AFT ages decrease monotonously from NW to SE until thrust faults along the two transects, with an age-jump across thrust F35. Joint thermal history modelling shows a three-stage cooling history as a result of denudation, especially with spatial differentiation in the first stage. Relative slow cooling at c. 0.6–1.0 °C/Ma occurred in the BQ and the northern part of the HQ transect during 220–100 Ma and the northern part of the CU transect during 160–100 Ma, respectively, with an amount of c. 2–3 km denudation between 160 and 100 Ma, implying little movement along the thrusts F13 and F33. In the middle and southern parts of the HQ transect and the southern part of the CU transect, rapid cooling at c. 4.0–7.0 °C/Ma, with c. 6–9 km denudation during 170–130 or 160–100 Ma, respectively, is probably influenced by thrusting of F35, F38 and F42 and the resultant tilting. A combination of thrusting, tilting, and denudation led to the youngering trends towards thrusts in different parts. However, there was no significant denudation across the Langshan Mountains in the second stage from c. 100 or 80 Ma until the last stage of rapid denudation (c. 2 km) since 20–10 Ma, which is simultaneous with the rapid uplift of the northern part of the Tibetan Plateau at c. 15 Ma. A youngering trend of AFT ages from the inner to the peripherals of the Mongolian Plateau implies the outward propagation of the Mongolian Plateau since the Mesozoic.